1983
DOI: 10.1113/jphysiol.1983.sp014806
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal interactions in cat retinal ganglion cells showing linear spatial summation.

Abstract: 3. These Q cells appear to form a homogeneous group which is probably a subset of the tonic W cells (Stone & Fukuda, 1974) or sluggish centre-surround cells (Cleland & Levick, 1974).4. The over-all spatio-temporal frequency characteristics of cells showing linear spatial summation are not separable in space and time. The form of the spatial frequency responsivity function of these cells depends upon the temporal frequency at which it is measured while the temporal phase of their response measured at any consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
220
0
2

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(245 citation statements)
references
References 23 publications
21
220
0
2
Order By: Relevance
“…For this minimization, we followed the standard approach described by Enroth-Cugell et al (1983), with one addition: the major and minor radii of the center were allowed to be different because we found that many cells had asymmetric centers. R (k) was then computed as:…”
Section: Analysis Of Receptive Field Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For this minimization, we followed the standard approach described by Enroth-Cugell et al (1983), with one addition: the major and minor radii of the center were allowed to be different because we found that many cells had asymmetric centers. R (k) was then computed as:…”
Section: Analysis Of Receptive Field Propertiesmentioning
confidence: 99%
“…To determine how the NPY cells affect the center and surround, we fit the spatial tuning curves from NPY cell-ablated retinas and controls to the predictions of a standard receptive field model, a difference-of-Gaussians model (Rodieck, 1965;Enroth-Cugell and Robson, 1966;Enroth-Cugell et al, 1983;Shapley and Lennie, 1985), and examined which parameters of the center and surround were different between the two groups. Six parameters were evaluated: the size of the center and surround, the strength of the center and surround, the asymmetry of the center, and the relative phase between the center and surround.…”
Section: Ablation Of Npy Cells Alters Spatial Tuning Of Ganglion Cellsmentioning
confidence: 99%
“…In addition to the phase shift caused by temporal filtering, center and surround can have transport delays that are temporal frequency-independent. The surround delay is constrained to be larger than the center delay, as characterized in cat ganglion cells (Derrington & Lennie, 1982;Enroth-Cugell et al, 1983;Frishman et al, 1987) and those of macaque (Lee et al, 1989a;Yeh et al, 1995).…”
Section: A Model Of Chromatic-temporal Interactionmentioning
confidence: 99%
“…All measurements were based on responses with fundamental component amplitudes in the range of 5-10 impulses s −1 . This is a range in which X-cell responses scale linearly with contrast (Enroth-Cugell et al, 1983;Troy & Enroth-Cugell, 1993). Responsivity is defined as the amplitude of the fundamental component divided by the contrast that evoked the response.…”
Section: Visual Stimulation and Data Collectionmentioning
confidence: 99%
“…From a number of studies, we know that the radius of the center of the X-cell receptive field is invariant with temporal frequency in the range 0.5 to 30 Hz at high photopic illuminance (Enroth-Cugell et al, 1983;Dawis et al, 1984;1993). At higher temporal frequencies, however, the X-cell center expands (Frishman et al, 1987;1993).…”
Section: Dependence Of Center Radius On Temporal Frequency Under Highmentioning
confidence: 99%